Prostaglandin E2 Inhibits Group 2 Innate Lymphoid Cell Activation and Allergic Airway Inflammation Through E-Prostanoid 4-Cyclic Adenosine Monophosphate Signaling - Zhou, Yu; Wang, Wei; Zhao, Conghui; Wang, Yan; Wu, Haoming; Sun, Xiuyuan; Guan, Youfei; Zhang, Yu (Frontiers in Immunology, 2018)
Evidence is accumulating that group 2 innate lymphoid cells (ILC2) play an important role in allergic airway inflammation by producing a large amount of type 2 cytokines. But it remains poorly understood how its activities are properly controlled in vivo. Here we demonstrated that PGE2 had a profound inhibitory effect on IL-33-induced ILC2 expansion and IL-5 and IL-13 production in vitro. This effect was mimicked by PGE1-alcohol but attenuated by ONO-AE3-208, indicating a selective action through the EP4 receptor. In the IL-33-induced asthma model, co-administration of PGE2 or PGE1-alcohol resulted in diminished IL-5 and IL-13 production, reduced eosinophilia and alleviated lung pathology. In contrast, EP4-deficient mice displayed an exacerbated inflammatory response in another ILC2-mediated asthma model induced by Alternaria extract. Mechanistic studies demonstrated that the PGE2-mediated inhibition of ILC2 was dependent on cAMP production. Further downstream, PGE2-EP4-cAMP signaling led to suppression of GATA3 and ST2 expression, which is known to be critical for ILC2 activation. These findings reveal a novel function of PGE2 as a negative regulator of ILC2 activation and highlight an endogenous counter-regulatory mechanism for the control of innate allergic inflammatory responses.